PROJECT-BASED LEARNING (PBL) AS A TOOL FOR DEVELOPING 21ST CENTURY SKILLS IN ENGLISH LANGUAGE CLASSROOMS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Project-Based Learning (PBL) represents a dynamic shift in EFL pedagogy, emphasizing authentic projects to simultaneously build linguistic proficiency and 21st-century skills like critical thinking, collaboration, communication, creativity, and problem-solving. This article synthesizes meta-analytic and empirical evidence, revealing moderate-to-large effects on academic achievement (SMD = 0.650) and motivation. Grounded in constructivist theories, it delves into PBL's structured cycles, digital integrations, and applications in diverse contexts, with a focus on Uzbekistan where PBL counters rote learning traditions. Challenges such as resource demands and assessment alignment are critiqued, alongside strategies for inclusive implementation. The discussion advocates PBL as essential for preparing EFL learners for global challenges, promoting holistic development through inquiry-driven, real-world engagements.